Formulation of Family Scale Laying Duck Farming Strategies Using Strategic Position and Action Evaluation Matrix - Nasir, Nasir; Suryandani, Hendy (Universitas Nusantara PGRI Kediri, 2023)
Research aim : The purpose of this study was to formulate a laying duck farming strategy by identifying internal and external environmental factors. Design/Method/Approach : The analysis was carried out through an analysis of strengths, weaknesses, opportunities and threats (SWOT) based on the results of interviews with the research object. Research Finding : The results of the SWOT analysis are quantitatively stated in a space matrix so that a position strategy and evaluation of its action are obtained. The results of space matrix show that laying duck farming were in strengths and threats combination, where the organization must diversify its strategy to face a number of formidable challenges. Theoretical contribution/Originality : - Practitionel/Policy implication : - Research limitation : - Keywords: Laying Duck, SWOT, Position Strategy, Action Evaluation